2017
DOI: 10.1080/13691058.2017.1384572
|View full text |Cite
|
Sign up to set email alerts
|

‘Safe’, yet violent? Women’s experiences with obstetric violence during hospital births in rural Northeast India

Abstract: The majority of maternal health interventions in India focus on increasing institutional deliveries to reduce maternal mortality, typically by incentivising village health workers to register births and making conditional cash transfers to mothers for hospital births. Based on over 15 months of ethnographically informed fieldwork conducted between 2015 and 2017 in rural Assam, the Indian state with the highest recorded rate of maternal deaths, we find that while there has been an expansion in institutional del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 28 publications
0
74
0
5
Order By: Relevance
“…Some Bengali Muslims used the word "sub-human" to describe their experience of childbirth and accessing health care. 11 This perception is reinforced, when we examine "native Assamese" and mainstream discourses that often label Bengali Muslims as "illegal immigrants". Bengali Muslims are blamed for "large" populations, unregulated fertility, and for poor health statistics in the areas where they live, and are perceived as being cunning and more adept at accessing state entitlements than the "native" population.…”
Section: Hierarchies Of Citizenshipmentioning
confidence: 99%
See 3 more Smart Citations
“…Some Bengali Muslims used the word "sub-human" to describe their experience of childbirth and accessing health care. 11 This perception is reinforced, when we examine "native Assamese" and mainstream discourses that often label Bengali Muslims as "illegal immigrants". Bengali Muslims are blamed for "large" populations, unregulated fertility, and for poor health statistics in the areas where they live, and are perceived as being cunning and more adept at accessing state entitlements than the "native" population.…”
Section: Hierarchies Of Citizenshipmentioning
confidence: 99%
“…Empirical work in Assam finds several instances of abuse in state facilities in rural Assam and argues that such violence is gendered " … and intersects with other axes of structural inequalities, such as caste/ethnicity, class and region in India, producing a negative and often violent experience of pregnancy and childbirth in India". 11 Using a mix of clinical observations and quantitative methods, a study based in state and private facilities in urban and rural Uttar Pradesh, North India, reveals that while all women experienced at least one type of mistreatment during childbirth across facilities, women who were either Scheduled Tribes or Scheduled Castes, as well as multiparous women, reported greater and more intense forms of mistreatment. 12 The latter include actions with significant possibilities of harm, such as extreme fundal pressure, using dirty rags to wipe the perineal area, physical abuse, and sexually humiliating comments.…”
Section: Context Of Disrespect and Abusementioning
confidence: 99%
See 2 more Smart Citations
“…In consonance with this, studies have documented the forms of D&AC childbearing women 4 have experienced in healthcare facilities. The women in these studies reported that they were physically abused [19], psychologically abused [19], detained for non-payment of bills [20], examined without consent [21,22], discriminated against because of their social status [21,22], denied of their choice of birthing position because of facility-recommended guidelines [22][23][24], and subjected to iatrogenic procedures such as episiotomies, in some instances done without anaesthesia, and with improper pelvic examinations [25]. This D&AC, Sen, Reddy & Iyer [26] argued, is driven by socioeconomic inequalities and institutional structures and processes.…”
mentioning
confidence: 99%